A combined heat and power (CHP) plant consisting of a microturbine and a Stirling engine. Issue 1 (February 2021) - Antipov, Y A; Smirnov, S V; Oshchepkov, P P; Khalife, H S
Abstract: Modern industrial development of governments is largely determined by the condition of the power industry. Nowadays, the energy policy of governments is focused on the improvement of highly efficient combined heat and power (CHP) plants, to conserve fossil fuels and achieve higher output power. The application of gas turbines and heat recovery systems is considered a promising method of increasing the overall efficiency of the power plant. In this article, a microturbine was considered as the prime mover in a CHP plant, while the exhaust gases were used to power a Stirling engine, and consequently generating additional power and heat, increasing the overall efficiency of the power plant. Also, the advantages and disadvantages of the Stirling engine were briefly discussed. Moreover, two general configuration schemes and a calculation method of the CHP plant have been developed. Finally, the results of utilizing the exhaust gases of a microturbine and a Stirling engine were presented.